Studi Filologis Sharh Isagoge: Menelusuri Logika Aristotelian di Kalangan Muslim Klasik - Koes Adiwidjajanto (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2012)
This article puts emphasis on Daljî, one of the traditional Muslim scholars, for his writing “Ta‘lîqât ‘alâ Sharh Shaykh Islâm Zakarîyyâ al-Ansârî li Matn Isaghuji”, with a philological approach. Such approach has been widely known in the Islamic world as tahqîq al-nusûs, which focuses on presenting part of the text readable in different time and context, so it can be used and read in accordance with the writer’s intention. What important from Daljî’s contribution in the study of traditional Aristotelian logic (mantiq) is that his defense on this study has a firm position, whereas another Sunnî Traditionalist especially the people who were known as Ahl al-hadîth like Ibn Salâh and Ibn Taymîyya considered it as innovation according to the authoritative Islamic teachings. In his ta‘lîq, Daljî followed the previous Muslim Scholar in writing a logical method that was considerably known amongst its experts. The topics discussed in this study deal with explanations on kulliyât (generals), qadâyâ (prepositions), al-‘aks wa al-tanâqud (the contradictions), qiyâsât (syllogism), on rhetoric and poetics.